2013
DOI: 10.1002/eji.201343750
|View full text |Cite
|
Sign up to set email alerts
|

Gimap3 and Gimap5 cooperate to maintain T‐cell numbers in the mouse

Abstract: Gimap3 (IAN4) and Gimap5 (IAN5) are highly homologous GTP-binding proteins of the Gimap family. Gimap3 and Gimap5, whose transcripts are abundant in mature lymphocytes, can associate with antiapoptotic Bcl-2 family proteins. While it is established that Gimap5 regulates T-cell survival, the in vivo role of Gimap3 is unclear. Here we report the preparation and characteristics of mouse strains lacking Gimap3 and/or Gimap5. We found that the number of T cells was markedly reduced in mice deficient in both Gimap3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…In Gimap5 tm1Wlr/WT there are no reported defects in hematopoiesis or on the mRNA expression of other Gimap family members in the thymus; these mice were described only as having a 50% reduction in Gimap5 expression (Schulteis et al 2008). This dosage effect on Gimap5 expression in heterozygotes has been consistently observed with two other independent murine Gimap5 null mutations at both the mRNA and protein level in Barnes et al (2010) and Yano et al (2014), suggesting a tight correlation between Gimap5 gene expression and protein abundance.…”
Section: The N Terminus Of Cast Gimap3 Impairs Protein Synthesismentioning
confidence: 72%
See 2 more Smart Citations
“…In Gimap5 tm1Wlr/WT there are no reported defects in hematopoiesis or on the mRNA expression of other Gimap family members in the thymus; these mice were described only as having a 50% reduction in Gimap5 expression (Schulteis et al 2008). This dosage effect on Gimap5 expression in heterozygotes has been consistently observed with two other independent murine Gimap5 null mutations at both the mRNA and protein level in Barnes et al (2010) and Yano et al (2014), suggesting a tight correlation between Gimap5 gene expression and protein abundance.…”
Section: The N Terminus Of Cast Gimap3 Impairs Protein Synthesismentioning
confidence: 72%
“…Gimap3 and Gimap5 are important for mtDNA segregation Our original cloning of Gimap3 as a modifier of mtDNA segregation (Jokinen et al 2010) was unable to determine whether other Gimap family members, in particular the paralogue Gimap5, may also contribute to this mtDNA phenotype. Recent evidence points to a cooperative genetic function between Gimap3 and Gimap5 in lymphocyte development (Yano et al 2014). To test Gimap5 for a role in mtDNA segregation, we took advantage of a germline knockout mouse Gimap5 tm1Wlr (Schulteis et al 2008).…”
Section: The N Terminus Of Cast Gimap3 Impairs Protein Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Again, some subsets use additional signaling components, such as SLAM Associated Protein (SAP, Sh2d1 ), but these are specialized requirements. Finally, there are additional signaling molecules such as the multiple related GTPases of the IMAP family (Gimap1–9), most of which are strongly expressed in a mature T-cell restricted way and maintain cell viability through pathways that are less well understood (Schwartzberg et al , 2009; Wang et al , 2010; Yano et al , 2014). …”
Section: Introduction: T-cell Identity and Processing Of T-cell Prmentioning
confidence: 99%
“…Only a few studies focusing on the function of GIMAPs in humans have been conducted to date. Previous animal studies have clearly shown GIMAPs to interact with known apoptosis regulators and have a role in the differentiation, survival, and apoptosis of T cells and some other cell types (7)(8)(9).…”
mentioning
confidence: 98%